Listen, sing and learn: the place of songs in primary FL learning in Portugal - Nobre, Ana Sofia Encarnação Cristino (2017)
Songs are known to young learners and present an excellent format for increasing interest and motivation to learn a foreign language. This action research study gave me the opportunity to find out when should teachers make use of a song over a thematic unit in a set of lessons and to find out when and how a song is most supportive for the learners’ language acquisition process. To obtain information about the impact of singing songs in the English classroom I undertook an empirical study with a group of fourteen learners and a control group of seventeen learners, based on an action research method, in a Portuguese public school. Data was collected through questionnaires, worksheets, self assessment grids, formal assessment test results and my teacher’s journal. Results that came up from reflective practice and systematic collection of data helped to clarify the importance of using songs repeatedly when compared to singing only once. However, results also show that the control group learners were able to acquire language without singing songs as often. It was possible to conclude that the use of songs repeatedly is meaningful to enable learners to acquire communicative abilities and literacy, it impacts on learners’ prosody and it influences learners’ motivation in the classroom.